2017
DOI: 10.1186/s41235-017-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

Embodied science and mixed reality: How gesture and motion capture affect physics education

Abstract: A mixed design was created using text and game-like multimedia to instruct in the content of physics. The study assessed which variables predicted learning gains after a 1-h lesson on the electric field. The three manipulated variables were: (1) level of embodiment; (2) level of active generativity; and (3) presence of story narrative. Two types of tests were administered: (1) a traditional text-based physics test answered with a keyboard; and (2) a more embodied, transfer test using the Wacom large tablet whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 52 publications
(57 reference statements)
2
83
0
7
Order By: Relevance
“…The advantages of PhET simulation could involve the interaction among students and teachers, build the knowledge students independently, discovery and combining of prior knowledge of students and improves interest in studying students. These results indicate conformity with previous studies showed PhET simulation can improve involvement and interaction among students, educate students to have the thinking patterns of constructivism, make learning more interesting because the students can learn while playing, and visualize the concepts of science in the form of models (Jauhari et al, 2017;Johnson-Glenberg & Megowan-Romanowicz, 2017;Setiadi & Muflika, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…The advantages of PhET simulation could involve the interaction among students and teachers, build the knowledge students independently, discovery and combining of prior knowledge of students and improves interest in studying students. These results indicate conformity with previous studies showed PhET simulation can improve involvement and interaction among students, educate students to have the thinking patterns of constructivism, make learning more interesting because the students can learn while playing, and visualize the concepts of science in the form of models (Jauhari et al, 2017;Johnson-Glenberg & Megowan-Romanowicz, 2017;Setiadi & Muflika, 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Construct c has been called sense of immersion in previous articles describing the Johnson-Glenberg embodiment taxonomy for education (Johnson-Glenberg et al, 2014a;Johnson-Glenberg and Megowan-Romanowicz, 2017). Slater's lab posits that immersion is a non-subjective property of the technological system (which includes attributes like Field of View (FOV) and fidelity to environment).…”
Section: Immersion/presencementioning
confidence: 99%
“…This lab has researched in mixed and augmented reality spaces for science education for over a decade; the range of topics includes geography (Birchfield and Johnson-Glenberg, 2010), nutrition science (Johnson-Glenberg and Hekler, 2013;JohnsonGlenberg et al, 2014b), simple machines (Johnson-Glenberg et al, 2015), physics (Johnson-Glenberg et al, 2014a, 2016 and forces. The full article describing the electric field study and the seven learning tasks can be found at Johnson-Glenberg and Megowan-Romanowicz (2017).…”
Section: Example Of An Embodied Lesson and Experimentsmentioning
confidence: 99%
See 2 more Smart Citations